Expanding the family of extracellular chaperones: Identification of human plasma proteins with chaperone activity. (4th October 2021) - Geraghty, Nicholas J.; Satapathy, Sandeep; Kelly, Megan; Cheng, Flora; Lee, Albert; Wilson, Mark R.
Abstract: Proteostasis, the balance of protein synthesis, folding and degradation, is essential to maintain cellular function and viability, and the many known intracellular chaperones are recognized as playing key roles in sustaining life. In contrast, the identity of constitutively secreted extracellular chaperones (ECs) and their physiological roles in extracellular proteostasis is less completely understood. We designed and implemented a novel strategy, based on the well‐known propensity of chaperones to bind to regions of hydrophobicity exposed on misfolding proteins, to discover new ECs present in human blood. We used a destabilized protein that misfolds at 37°C as "bait" to bind to potential ECs in human serum and captured the complexes formed on magnetic beads. Proteins eluted from the beads were identified by mass spectrometry and a group of seven abundant serum proteins was selected for in vitro analysis of chaperone activity. Five of these proteins were shown to specifically inhibit protein aggregation. Vitronectin and plasminogen activator‐3 inhibited both the in vitro aggregation of the Alzheimer's β peptide (Aβ 1–42 ) to form fibrillar amyloid, and the aggregation of citrate synthase (CS) to form unstructured (amorphous) aggregates. In contrast, prothrombin, C1r, and C1s inhibited the aggregation of Aβ 1–42 but did not inhibit CS aggregation. This study thus identified five novel and abundant putative ECs which may play important roles in the maintenance of extracellular proteostasis, and which apparently have differing abilities to inhibit the amorphous and amyloid‐forming protein aggregation pathways.